PEMBUATAN WEBSITE QUALITY CONTROL AND INVENTORY (QCAI) SILO PENAMPUNGAN SEMENTARA (STUDI KASUS PT XYZ) - azhar, dicky maulana (Universitas Muhammadiyah Gresik, 2024)
PT XYZ is a company specializing in managing premium rice for distribution across various regions. To ensure quality and accurate inventory management, the company has developed a Quality Control and Inventory (QCAI) website. This website was designed based on direct observations of production processes, quality control, and inventory recording in storage silos, as well as interviews with relevant stakeholders. Utilizing a System Management Information (SIM), the website implements the first in first out (FIFO) method to manage inventory and monitor rice quality in real time. Its key features include quality control recapitulation and an automated alarm system to prevent errors in silo filling. This system ensures smooth operations, reduces the risk of mistakes, and consistently maintains the quality standards of the rice.